Pengaruh Konsumsi Putih Telur pada Lansia dengan Hipertensi - Pudjiati Pudjiati; Yeti Resnayati; Tjutju Rumijati; Nelly Yardes; Eska Riyanti (Jurnal Keperawatan, 2023)
WHO (2016) states that one in three adults worldwide has high blood pressure and this increase occurs with age, from one in ten people in their 20s and 30s to five in ten people in their 50s. In Indonesia, based on the 2018 Riskesdas, the prevalence of hypertension was 45.9% at the age of 55-64 years, 57.6% at the age of 65 years, 74% and 63.8% at the age of 75 years. Research conducted by dr. Zhipeng Yu from Jilin University, China, mentioned that the content in egg whites called RVPSL can indeed nourish blood vessels and reduce the risk of hypertension. This study aims to determine the effect of giving egg whites on reducing blood pressure in the elderly with hypertension. The research design is quasi-experimental with one group pretest-posttest. The samples used were 40 elderly people with hypertension. The analytical method used is the Paired t test. The results of data analysis showed that there was a significant difference in the first measurement of Systole before and after the intervention (p value = 0.001) with a greater difference in average value (difference value = 11.257 mmHg). while in the first measurement of diastole, the results of the analysis showed that there was a significant difference before and after the intervention (p value = 0.001), the average difference after the intervention (difference value = 7.980 mmHg). Consumption of egg whites on a regular basis and increases the work of ACE in the vessels which allows obtaining blood pressure stability. The conclusion is that there is a significant decrease in blood pressure in the elderly with hypertension by 8 to 11 mmHg after giving 1 egg white for 5 weeks.